SOSIALISASI PENGELOLAAN SAMPAH RUMAH TANGGA ORGANIK DAN NON-ORGANIK UNTUK KESEHATAN LINGKUNGAN DI DESA BULU CINDEA, KABUPATEN PANGKEP - Fitri Indah Yani; Rahmi Rahmi; Asrianti Syarif; Juliani Ibrahim; Nurinsana Salam; Syamsia Syamsia; Andi Chadijah; Abd. Rakhim Nanda (Universitas Mataram, 2023)
The active role of residents in managing household waste is very important, especially in reducing the amount of waste piled up. It can be said that the waste problem in the Bulu Cindea Village environment is that residents are not yet able to manage organic and non-organic waste properly. If it continues, it will cause environmental pollution and harm people's health. Therefore, this outreach activity was carried out so that the residents of Bulu Cindea village could understand the importance of household waste management. In this activity, outreach is carried out to increase public awareness in managing organic and non-organic household waste independently and can be carried out well. This waste management will be felt to be effective because it will directly and actively involve village residents. From the results of community outreach in Bulu Cindea village, the community began to manage household organic and non-organic waste independently, was able to improve the waste management system, was able to reduce piles of rubbish which could cause various diseases and the environment around where they lived became cleaner, more comfortable and Healthy.